Experimental and simulation studies of iron oxides for geochemical fixation of CO2-SO2 gas mixtures - García, Susana (2010)
Successful geological sequestration of carbon in deep saline aquifers as a technological strategy to reduce CO2 emissions and combat climate change requires accurate predictive models of rock-brine-C0 2 interactions, which need to be validated and refined through comparisons with laboratory experiments. The main objective of this Thesis is to study, experimentally and theoretically, whether iron oxides-containing subsurface formations would be potential reservoirs for sequestering CO2-SO2 gas mixtures derived from fossil fuel combustion processes. Benefits could be then derived of co-injecting sulfur with C0 2-dominated gas streams. Experiments were conducted with two natural samples, hematite (aT^C^) and goethite (a-FeOOH), using a high pressure-high temperature system designed to simulate conditions in geologic formations deeper than 800 m, where the supercritical state of CO2 can be taken advantage of. Solid samples were allowed to react with a NaCl-NaOH brine and S0 2-bearing CC^-dominated gas mixtures. Reacted solids were examined for mineralogical changes and collected fluids analysed to provide data on the fate of dissolved species. Experimentally, brine composition and SO2 content of the gas stream greatly influenced the pH of the system as well as mineralogical changes. Increasing reaction times, fine powders (< 38 pm), low values of solids concentration (lOg/L) and reaction temperatures up to 100°C enhanced minerals dissolution and precipitation of secondary phases. Carbonates precipitates, siderite (FeCCh) and dawsonite (NaAl(0H)2C0 3), were observed as a result of the experiments along with some S-bearing phases and some residual salt. Reaction pressure was seen to have a major effect on availability of dissolved SO2 and CO2.